The methodological trap: In reply to Kemp and Owen. Issue 1 (January 2017) - Harvey, Bruce
Highlights: External Affairs cannot substitute for Social Performance in extractive industries. External Affairs is a communication-based corporate function. Social Performance should be asset-based and behaviour focussed. Good Social Performance should work off internal competencies, termed "in-reach". "In-reach" values comprehension ahead of compliance and "outreach". Abstract: I thank my colleagues Prof. Deanna Kemp and Dr. John Owen for their thoughtful critique and valuable prompt to expand my exposition on Social Performance "in-reach" in the extractive sector (Kemp and Owen, 2016). My response is in two parts. I lead by briefly recounting context and describing what I believe is the major issue alive in the extractive sector today as it attempts to interface constructively with society – the major issue is methodological conflation of Social Performance and External Affairs. In doing this I will demonstrate that Kemp, Owen and I are essentially on the same page. Second, I set out my clarification of the semantic and other differences that lie between us regarding good Social Performance. I conclude by reprising my argument that the methodological divide lies elsewhere.